How to Deal with Climate Change?: Institutional Adaptive Capacity as a Means to Promote Sustainable Water Governance - Mosello, Beatrice (Springer, 2015)
s the evidence for human-induced climate change becomes more obvious, so too does the realisation that it will harshly impact on the natural environment as well as on socio-economic systems. Addressing the unpredictability of multiple sources of global change makes the capacity of governance systems to deal with uncertainty and surprise essential. However, how all these complex processes act in concert and under which conditions they lead to the sustainable governance of environmental resources are questions that have remained relatively unanswered. This book aims at addressing this fundamental gap, using as case examples the basins of the Po River in Northern Italy and the Syr Darya River in Kyrgyzstan. The opening chapter addresses the challenges of governing water in times of climate and other changes. Chapter Two reviews water governance through history and science. The third chapter outlines a conceptual framework for studying institutional adaptive capacity. The next two chapters offer detailed case studies of the Po and Syr Darya rivers, followed by a chapter-length analysis and comparison of adaptive water resources management in the two regions. The discussion includes a description of resistant, reactive and proactive institutions and puts forward ideas on how water governance regimes can transition from resistant to proactive. The final chapter takes a high-level view of lessons learned and how to transform these into policy recommendations and offers a perspective on embracing uncertainty and meeting future challenges.